Pengaruh Corporate Governance Terhadap Manajemen Laba Riil(Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia) - Kusumawati, Eny; , Dra Rina Trisnawati, Ak. MSi, Ph.D; , Drs. Ahmad Mardalis, MBA (2015)
This research aims to determine the effect of corporate governance on the real earnings management, occured in companies listed in Indonesia Stock Exchange during 2006-2010 period. Corporate governance measurement used structural approach consist of the percentage of institutional ownership, manajerial ownership, the proportion of the board independent commissioner, the size of board commissioners and the existence of an audit committee. While, earnings management measurement used real approach. This study used purposive sampling method. These samples are 160 companies. Analysis used multiple regression analysis. Research results indicate that corporate governance including institutional ownership, manajerial ownership, the proportion of the board independent commissioner, and the existence of an audit committee have effect on real earnings management. While, the size of board commissioners do not effect on the real earnings management.